The effects of physical activity during childhood, adolescence, and adulthood on cardiovascular risk factors among adults - Werneck, André O [UNESP]; Agostinete, Ricardo R. [UNESP]; Lima, Manoel Carlos S de [UNESP]; Turi-Lynch, Bruna C.; Fernandes, Romulo A. [UNESP] (FapUNIFESP (SciELO), 2019)
OBJECTIVES: To analyze the association between physical activity during life and cardiovascular risk factors among adults. DESIGN: The sample was composed of 101 adults (59 men) between 30 and 50 years old, who were recruited from different gyms and from a University in Brasil. Participants were divided according to their engagement in sports in early life (self-reported) and current physical activity (pedometer) (sports participation during childhood/adolescence and currently active [n=26], sports participation during childhood/adolescence and currently inactive [n=26], and control [n=49]). Cardiovascular risk factors were measured, such as body fat (through DXA), HDL-C, triglycerides, HOMA index, systolic blood pressure, diastolic blood pressure, and C-reactive protein. We adopted the covariates of chronological age, sex, alcohol consumption, tobacco, and body mass index. General estimating equations were used, with p<0.05. RESULTS: After the adjustments of the final model, individuals engaged in sports during childhood and adolescence and inactive during adulthood presented lower body fat, when compared to participants persistently inactive (p<0.001). Participants persistently active presented lower body fat (p<0.001) and lower c-reactive protein (p=0.010) when compared to the control group. CONCLUSION: Early sports participation was associated with reduced body fat, and being physically active throughout life was associated with reduced body fat and C-reactive protein.